Development Of Diffusion Barrier-Forming Coating For High-Temperature Application: Effect Of Coating Duration And Bath Temperature - Hiew, Wai Kien (Universiti Sains Malaysia, 2022)
During the combustion of biomass, it will release chlorine, potassium, sulfur, nitrogen, and silicon. The presence of a high concentration of chlorine and alkali content from biomass fuels can cause severe damage to the combustion units. The biggest concern of the superheater material in biomass plants is the issue of corrosion during high-temperature combustion of biomass. The interdiffusion between coating and the material has affected the lifespan of the superheater. In order to solve this issue, it is suggested to apply a barrier coating to mitigate the interdiffusion of the coating elements to the material of the wall of the superheater. Molybdenum is chosen as the coating element due to its excellent properties. Molybdenum is very difficult to coat on the surface of stainless steel. In this study, the effect of bath temperature ranges between 30-35 ºC, 40-45 ºC, and 50-55 ºC and different coating duration which is 1 hour, 2 hours and 3 hours were studied to determine the effect of temperature and coating duration towards molybdenum coating on the surface of stainless steel 304. The surface of coating was analysed using FESEM with EDX and XRD. Based on the surface morphology and elemental analysis and the cross-sectional area, both of the characterization result had proved presence of molybdenum on stainless steel at different temperature and duration. Result of elemental analysis had detect highest percent of molybdenum at 40-45 ºC after 3 hour deposition.